PERENCANAAN SISTEM PENDATAAN DAN PELAPORAN KEGIATAN PEMBANGUNAN - Adelina, Letty (Jurnal Ilmu Administrasi Negara, 2016)
Data Collection and Reporting System Planning Development Activities. The purpose of this study is to identify and analyze the data collection and reporting system planning development activities in the administration and development of electronic data Pekanbaru City Secretariat as well as factors that hinder the planning system-based data collection and reporting applications. This study used descriptive qualitative approach. The informants are sections and sub sections finance program and project implementation related SKPD. The technique of collecting data through interviews, observation and document engineering. Analysis of data through data reduction, data presentation, verification and conclusion. Based on the results of research, planning data collection and reporting system is divided into four stages, namely planning, establishment plan, control plans and evaluating the implementation of the plan. While the factors that hinder the planning of this system is the absence of regulation, weak human resources, lack of effective supervision, lack of commitment, the effects of mutations and the problem period.